THE RELATIONSHIP BETWEEN AUTHORITARY PARENTING PATTERNS AND AGGRESSIVE BEHAVIOR IN STUDENTS OF AULIA CENDEKIA ISLAMIC BOARDING SCHOOL, PALEMBANG - Andi, Cessha; Noviza, Neni; Marianti, Lena (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Aggressive behavior in adolescents is a significant issue, including in the Islamic boarding school environment. One factor that can influence aggressiveness is authoritarian parenting, which is characterized by tight control and minimal communication between parents and children. This study aims to analyze the relationship between authoritarian parenting and aggressive behavior in students at the Aulia Cendekia Palembang Islamic Boarding School. This study uses a quantitative method with a correlational type. Respondents in the study were 49 MTs level students, who were selected using a purposive sampling technique. Data were collected using a questionnaire and analyzed using the Pearson Product Moment correlation test. The results showed a significant relationship, namely r count 0.612> r table 0.281 with a significance level <0.001 <0.05. Thus, the alternative hypothesis (Ha) can be accepted with the specified significance level. This means that the higher the authoritarian parenting pattern applied by parents, the higher the tendency for aggressive behavior in students.